Social engagement and cognitive function among middle-aged and older adults: gender-specific findings from the Korean longitudinal study of aging (2008–2018) - Sarah Soyeon Oh (Nature Portfolio, 2021)
Abstract Recent findings suggest that social disengagement in later life may result in cognitive decline and increase risk of Alzheimer’s and related dementias. However, little is known regarding the gender-specific longitudinal association between social engagement and cognition among middle-aged and older adults. Using data from a nationally representative sample of 2707 men and 5196 women from the Korean longitudinal study of aging, we examined the gender-specific association between social activity and cognitive function. Results from the generalized estimating equation model showed that compared to individuals with consistent social engagement (religious, senior center, sport, reunion, voluntary, political), individuals with inconsistent engagement had lower cognitive function. Transitioning from engagement to non-engagement was associated with lower cognitive function among men only. Not being part of a senior center was associated with decreased cognitive function among both genders, while not being part of a religious group was significant for women only. While marital status was a significant predictor of cognitive ability for women, depression was a significant predictor for men. These findings have implications for policy-makers as interventions targeting improved cognitive function among middle-aged and older adults may be more effective when gender-specific predictors are taken into consideration.